Subsistence and Economy at the Calchaquí Valley (Salta, Argentina) during the Regional Developments Period (ca. 1000-1430 AD): Zooarchaeology of Las Pailas locality - Belotti López de Medina, Carlos Raúl (2015)
A detailed analysis of two faunal assemblages fromLas Pailas ? SsalCac18 (1) archaeological locality, in the northern section of the Calchaquí Valley (Salta province, Argentina), dated to the Regional Developments Period (ca. AD 1000-1430), is presented. Las Pailas was a large urban settlement, inhabited throughout most of the aforementioned Period. The assemblages come from two trash-dumps of different sizes. The smaller one (Structure 2) was found in a space formed between the walls of two rooms. The other dump (Test pit 3) is much bigger, it belongs to a 140 centimeters thick archaeological deposit situated in the town?s outer limits. As both assemblages reflect different lengths of time of accumulation, the analysis was aimed at approaching the relationship between a global strategy for the management of faunal resources at Las Pailas (Test pit 3), and its adaptation to particular constraints in a shorter time (Structure 2). The data presented here contributes to enlarge our knowledge of the geographical and historical variability of the zooarchaeological record of the center and northern Calchaquí Valley.